Zingiber officinale: Its antibacterial activity on Pseudomonas aeruginosa and mode of action evaluated by flow cytometry. (June 2017) - Chakotiya, Ankita Singh; Tanwar, Ankit; Narula, Alka; Sharma, Rakesh Kumar
Abstract: Biofilm formation, low membrane permeability and efflux activity developed by Pseudomonas aeruginosa, play an important role in the mechanism of infection and antimicrobial resistance. In the present study we evaluate the antibacterial effect of Zingiber officinale against multi-drug resistant strain of P. aeruginosa . The study explores antibacterial efficacy and time-kill study concomitantly the effect of herbal extract on bacterial cell physiology with the use of flow cytometry and inhibition of biofilm formation. Z. officinale was found to inhibit the growth of P. aeruginosa, significantly. A major decline in the Colony Forming Units was observed with 3 log10  at 12 h of treatment. Also it is found to affect the membrane integrity of the pathogen, as 70.06 ± 2.009% cells were found to stain with Propidium iodide. In case of efflux activity 86.9 ± 2.08% cells were found in Ethidium bromide positive region. Biofilm formation inhibition ability was found in the range of 68.13 ± 4.11% to 84.86 ± 2.02%. Z.officinale is effective for killing Multi-Drug Resistant P. aeruginosa clinical isolate by affecting the cellular physiology and inhibiting the biofilm formation. Graphical abstract: Highlights: The rhizome extract of Z. officinale was found to inhibit the growth of Pseudomonas aeruginosa, significantly. A major decline in the Colony Forming Units was observed with 3 log10  at 12 h of treatment. It strongly affects the membrane integrity of the pathogen, as 70.06 ± 2.009% cells were found to stain with Propidium iodide. In case of efflux activity 86.9 ± 2.08% cells were found in Ethidium bromide positive region. The extract is also effective in inhibiting the biofilm formation of P. aeruginosa.